Вітання ювіляру! (до 70-річчя професора Бойка Михайла Федосійовича) - Ходосовцев, О.Є.; Мойсієнко, І.І.; Загороднюк, Н.В. (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
Вітання ювіляру! (до 70-річчя професора Бойка Михайла Федосійовича)